2021
DOI: 10.3390/molecules26020387
|View full text |Cite
|
Sign up to set email alerts
|

Novel Methods to Manipulate Autolysis in Sparkling Wine: Effects on Yeast

Abstract: Sparkling wine made by the traditional method (Méthode Traditionelle) develops a distinct and desirable flavour and aroma profile attributed to proteolytic processes during prolonged ageing on lees. Microwave, ultrasound and addition of β-glucanase enzymes were applied to accelerate the disruption of Saccharomyces cerevisiae, and added to the tirage solution for secondary fermentation in traditional sparkling winemaking. Scanning electron microscopy and flow cytometry analyses were used to observe and describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…These differences were not evident until 18 months of bottle storage and reflect both decreases in proline concentration in control and ultrasound treated wines and increases in microwave and enzyme-treated wines relative to their respective concentrations at six months. This was possibly related to treatment-induced stress on the yeast that triggered cell degradation [4,9] and autolysis associated with longterm cellular degradation previously reported by Gnoinski et al [50] who found that yeast cell walls were permeable to propidium iodide ingress following microwave, ultrasound, and enzyme treatments. Similar to reports by Moreno-Arribas et al [16], proline was the predominant amino acid in the wines.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…These differences were not evident until 18 months of bottle storage and reflect both decreases in proline concentration in control and ultrasound treated wines and increases in microwave and enzyme-treated wines relative to their respective concentrations at six months. This was possibly related to treatment-induced stress on the yeast that triggered cell degradation [4,9] and autolysis associated with longterm cellular degradation previously reported by Gnoinski et al [50] who found that yeast cell walls were permeable to propidium iodide ingress following microwave, ultrasound, and enzyme treatments. Similar to reports by Moreno-Arribas et al [16], proline was the predominant amino acid in the wines.…”
Section: Discussionmentioning
confidence: 90%
“…We attribute this to hydrolytic activity that led to the degradation of yeast cell walls making membranes more susceptible to degradation. Prior work in our laboratory reported observations of increased numbers of cavitated yeast cells in response to the ultrasound and β-glucanase enzyme treatments relative to the control at tirage [50].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…It is indeed a common misconception especially when looking for the most prestigious cuvees. 15 During prolonged aging on lees, champagne and other sparkling wines develop distinct and desirable flavors and aroma profiles attributed to the proteolytic processes characteristic of yeast autolysis as recently described in minute details by Gnoinski et al 16 Yeast autolysis usually begins between two and four months after the second in-bottle fermentation. 17 Induced by a lack of nutrients combined with high levels of ethanol and dissolved CO 2 , low pH (∼3−3.5), and low temperature (12−14 °C) storage conditions, the irreversible degradation of several yeast cell-wall components occurs, such as glucans and mannoproteins for example.…”
Section: Introductionmentioning
confidence: 99%